An insight into bisphenol A, food exposure and its adverse effects on health: A review - Manzoor, Muhammad Faisal; Tariq, Tayyaba; Fatima, Birjees; Sahar, Amna; Tariq, Farwa; Munir, Seemal; Khan, Sipper; Nawaz Ranjha, Muhammad Modassar Ali; Sameen, Aysha; Zeng, Xin-An; Ibrahim, Salam A. (Frontiers in Nutrition, 2022)
Bisphenol A (BPA) is a synthetic chemical widely employed to synthesize epoxy resins, polymer materials, and polycarbonate plastics. BPA is abundant in the environment, i.e., in food containers, water bottles, thermal papers, toys, medical devices, etc., and is incorporated into soil/water through leaching. Being a potent endocrine disrupter, and has the potential to alter several body mechanisms. Studies confirmed its anti-androgen action and estrogen-like effects, which impart many negative health impacts, especially on the immune system, neuroendocrine process, and reproductive mechanism. Moreover, it can also induce mutagenesis and carcinogenesis, as per recent scientific research. This review focuses on BPA's presence and concentrations in different environments, food sources and the basic mechanisms of BPA-induced toxicity and health disruptions. It is a unique review of its type because it focuses on the association of cancer, hormonal disruption, immunosuppression and infertility with BPA. These issues are widespread today, and BPA significantly contributes to their incidence because of its wide usage in daily life utensils and other accessories. The review also discusses researched-based measures to cope with the toxic chemical.